Pedagogical Opportunities of Developing Professional Qualities in Religious Studies Students Based on English Language Materials (Eurasian Research Bulletin, 2022)
Teaching tools are considered a vital part of teaching process. Teaching tools should based on such kind of approach, which can serve as the main factor that students can use the situations they encounter outside the classroom and in the classroom as well. If students can use English in authentic context, the teaching outcome might be considered as achieved. Since the learning outcomes are assigned before conducting the lesson, the main target is to achieve this goal. Here competence-based approach can be helpful, as its main target is to coincide the outcome and expectation of the lesson plan. In this article below the opportunities of competence approach will be revealed in religious studies major through English language materials, particularly through handouts. Future theologians should acquire some professional qualities and how to get them through English materials will be discussed below